Is There a Faction in This List?. Issue 2 (July 2020) - De Weerdt, Hilde; Ho, Brent; Wagner, Allon; Qiao, Jiyan; Chu, Mingkin
Abstract: This article has two main objectives. First, we aim to revisit debates about the structure of Song Dynasty faction lists and the relationship between eleventh- and twelfth century factional politics on the basis of a large-scale network analysis of co-occurrence ties reported in the prose collections of those contemporary to the events. Second, we aim to innovate methodologically by developing a series of approaches to compare historical networks of different sizes with regard to overall network metrics as well as the significance of particular attributes such as native and workplace in their makeup. The probabilistic and sampling methods developed here should be applicable for various kinds of historical network analysis. The corresponding data can be found here: https://doi.org/10.17026/dans-xtf-z3au .